Distributional consequences of labor-demand shocks: the 2008-09 recession in Germany - Bargain, Olivier; Immervoll, Herwig; Peichl, Andreas; Siegloch, Sebastian (Munich, 2011)
"The distributional consequences of the recent economic crisis are still broadly unknown. While it is possible to speculate which groups are likely to be hardest-hit, detailed distributional studies are still largely backward-looking due to a lack of real-time microdata. This paper studies the distributional and fiscal implications of output changes in Germany 2008-09, using data available prior to the economic downturn. We first estimate labor demand on 12 years of detailed, administrative matched employer-employee data. The distributional analysis is then conducted by transposing predicted employment effects of actual output shocks to household-level microdata. A scenario in which labor demand adjustments occur at the intensive margin (hour changes), close to the German experience, shows less severe effects on income distribution compared to a situation where adjustments take place through massive layoffs. Adjustments at the intensive margin are also preferable from a fiscal point of view. In this context we discuss the cushioning effect of the tax-benefit system and the conditions under which German-style work-sharing policies can be successful in other countries. "